PENGUJIAN FINANCIAL FRAUD PADA PERBANKAN MALAYSIA: SUATU PENDEKAAN PELAPORAN - Kevin Andrew Oktavianus; Hisar Pangaribuan (Jurnal Ekonomis, 2020)
Financial statement are the results of financial reporting that are recorded during a certain period based on the company’s activities. This research generally aims to detecting financial fraud using fraud pentagon theory consisting of pressure, opportunity, rationalization, competence, and arrogance in financing company in Malaysia for the period 2017-2019. The data used in the study are secondary data in the form of annual report and financial report of the companies listed in Malaysia Stock Exchange. The results of this study found financial stability can be used to detecting financial fraud. Meanwhile, change of director, ineffective monitoring, and number of CEO’s picture cannot be used to detecting financial fraud. Aside from that, change in auditor cannot be tested because there is no external auditor change during the period.